The Beaver Yearbook, 1954 - Ray City Community Library, Ray City Community Library (Ray City School, 1954)
The Beaver, Ray City School Yearbook, 1954. Ray City School. CA014-002: Ray City Community Library, 1949-1954 Series. Ray City Community Library Collection.
The Beaver, Ray City School Yearbook, 1954. 1 electronic record (PDF), 21.1 MB (22,174,019 bytes)
Keywords: Berrien County (Ga.); Ray City (Ga.); Ray City School; Yearbooks